Knowledge, attitude, practice and associated factors among patients with type 2 diabetes in Cotonou, Southern Benin - Alaofè, Halimatou; AMOUSSA HOUNKPATIN, WALIOU BODOURIN AYANDA; DJROLO, FRANÇOIS; Ehiri, John; Rosales, Cecilia (My University, 2021)
Background: Type 2 diabetes (T2D) is becoming an epidemic with significant disability and premature death in Sub-Saharan Africa, including Benin. However, little is known about the level of knowledge, attitude, and practice (KAP) necessary for diabetic patients to enhance therapeutic outcomes and prevent diabetes complications. The study aimed to assess patients’ KAP levels and identify the factors associated in Cotonou, southern Benin. Methods: A cross-sectional study was conducted from July to August 2019 among 300 diabetic patients from four health centers. Data was collected using validated questionnaires. KAP levels were determined by calculating the scores, and multivariate logistic regression was used to explore factors influencing KAP scores. Results: About 53, 52, and 47% of all patients had good knowledge, attitude, and practice towards diabetes. In logistic regression, factors such as being female, married, educated, government/non-government employee, and longer duration of diabetes were significantly associated with good knowledge. Being married, having a longer duration of diabetes, and good knowledge were significantly associated with a good attitude while being educated, having a longer duration of diabetes, and good knowledge with good practice. Conclusions: Lack of knowledge, poor attitude, and inadequate practice were found in this surveyed community, suggesting a need for structured educational programs to assist diabetic patients. However, education should be considered a priority for male, newly diagnosed, and uneducated patients.
Keywords: Type 2 diabetes; Knowledge; Attitude; Practice; Benin